Global collaboration and media literacy: a critical analysis of international cases of educational media management and participation - Niño Romero, Mónica (2025)
In today’s society, media literacy is the key to effective education and critical and participatory citizenship; however, much remains to be done for media education to be effectively integrated and reach the majority of people. The study aims to assess how different media projects contribute to media literacy and critical education of audiences in North America, Latin America and Europe. To this end, a content analysis was carried out of initiatives such as The Learning Network of the New York Times, USMPTV in Peru, The Economist Educational Foundation in the United Kingdom, Público na Escola in Portugal, and the initiatives of Fundación Atresmedia in Spain (Mentes AMI, Efecto MIL and Amibox). The main results reveal that collaborations between media and education strengthen people’s ability to critically analyse media information, as these programmes not only offer educational resources, but also promote informed and engaged citizenship. Finally, the research highlights the need for comprehensive and sustainable approaches that ensure equitable access and adequate training of educational personnel, overcoming technological and socio-cultural limitations.